Edukasi Peran Pemuda Desa Beji dalam Meningkatkan Moral Politik untuk Pemilu 2024 - Bahri, Seful; Suprianto, Sekar Pramudya Wardani; Faadhillah, Farah (Jurnal Bina Desa, 2025)
Education shapes the mentality and quality traits that are instilled in society. Through a comprehensive education, individuals understand the importance of a vote-based system, citizen freedom and commitment, and morals on legislative issues. The education system must provide satisfactory information and foster a positive perspective regarding political obligations. Youth play an important role in maintaining stability and momentum as we enter the political year. As many as 70% of generation z or millennials who are starting to turn 17 say they will vote but still don't know how to start, and how to participate in elections. Departing from this problem is the beginning of the formation of a habit of passive political participation in society. Therefore, this educational program aims to expand and strengthen the role of the youth of Beji Village in raising awareness regarding political education and new voters to provide output for a better and more democratic Indonesia, by collaborating with village officials, the supervisory committee, and the youth of Beji Village, Tulung District, opening the first step in building a village for Indonesia in terms of democracy.